Prediction of Freezing of Gait in Parkinson's Disease Using Unilateral and Bilateral Plantar-Pressure Data - Pardoel, Scott; Nantel, Julie; Kofman, Jonathan; Lemaire, Edward D. (Frontiers in Neurology, 2022)
Freezing of gait (FOG) is a walking disturbance experienced by people with Parkinson’s disease (PD), and linked to falling, and reduced mobility. Wearable-sensor based devices can detect freezes in progress and provide a cue to help resume walking. While this is helpful, predicting FOG episodes before onset and providing a timely cue may prevent the freeze from occurring. Wearable sensors mounted on various body parts have been used to develop FOG prediction systems. Despite the known asymmetry of PD motor symptom, the difference between the most affected side (MAS) and least affected side (LAS) is rarely considered in FOG detection and prediction studies. To examine the effect of using data from the MAS, LAS, or both limbs for FOG prediction, plantar-pressure data were collected during walking trials and used to extract time and frequency based features. Three datasets were created using plantar pressure data from the MAS, LAS, and both sides together. Relief-f feature selection was performed. Prediction models were trained using the top 5, 10, 15, 20, 25 or 30 features for each dataset. The best models were the MAS model with 15 features, and the LAS and bilateral models with 5 features. The LAS model had the highest sensitivity (79.5%) and identified the highest percentage of FOG episodes (94.9%). The MAS model achieved the highest specificity (84.9%) and lowest false positive rate (1.9 false positives/walking trial). Overall, the bilateral model was best with 77.3% sensitivity and 82.9% specificity. Furthermore, the bilateral model identified 94.2% of FOG episodes an average of 0.8 s before FOG onset. Compared to the bilateral model, the LAS model had a higher false positive rate; however, the bilateral and LAS models were similar in all other evaluation metrics. The LAS model would have similar FOG prediction performance to the bilateral model at the cost of slightly more false positives. Given the advantages of single sensor systems, the increased false positive rate may be acceptable to people with PD. Therefore, a single plantar-pressure sensor placed on the LAS could be used to develop a FOG prediction system and produce performance similar to a bilateral system.